2016
DOI: 10.1097/md.0000000000002628
|View full text |Cite
|
Sign up to set email alerts
|

Injury of the Ascending Reticular Activating System in Patients With Fatigue and Hypersomnia Following Mild Traumatic Brain Injury

Abstract: We report on patients with post-traumatic fatigue and hypersomnia who showed injury of the lower portion of the ascending reticular activating system (ARAS) between the pontine reticular formation (RF) and the intralaminar thalamic nucleus (ILN) following mild traumatic brain injury (TBI), using diffusion tensor tractography (DTT).Two patients with mild TBI resulting from a car accident were enrolled in this study. Patient 1 was a 51-year-old woman showed abnormalities as 6.9 (cut off: 3.7 points) and 18 (cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 17 publications
1
58
0
3
Order By: Relevance
“…Most problems in diagnosis of TAI in patients with concussion or mild TBI have originated from this insensitivity of conventional CT and MRI. By contrast, since development of DTI, many studies have detected TAI lesions in patients with mild TBI who showed normal conventional CT or MRI [6][7][8][9][10][11][12][13][14]. Based on these results, normal conventional CT or MRI findings in patients with concussion or mild TBI is not an indication that the patient's brain is in a normal state without TAI lesions, therefore, conventional CT and MRI should not be mainly used for diagnosis of TAI in patients with concussion or mild TBI [9,34].…”
Section: Problems In Diagnosis Of Cerebral Concussion and Mild Tbimentioning
confidence: 99%
See 4 more Smart Citations
“…Most problems in diagnosis of TAI in patients with concussion or mild TBI have originated from this insensitivity of conventional CT and MRI. By contrast, since development of DTI, many studies have detected TAI lesions in patients with mild TBI who showed normal conventional CT or MRI [6][7][8][9][10][11][12][13][14]. Based on these results, normal conventional CT or MRI findings in patients with concussion or mild TBI is not an indication that the patient's brain is in a normal state without TAI lesions, therefore, conventional CT and MRI should not be mainly used for diagnosis of TAI in patients with concussion or mild TBI [9,34].…”
Section: Problems In Diagnosis Of Cerebral Concussion and Mild Tbimentioning
confidence: 99%
“…Regarding the demonstration of TAI in live human patients with concussion or mild TBI, in 2002, Arfanakis et al [6] reported on TAI lesions in patients with mild TBI using DTI for the first time. Subsequently, TAI has been demonstrated in patients with concussion or mild TBI in hundreds of studies [6][7][8][9][10][11][12][13][14].…”
Section: Diagnostic History Of Traumatic Axonal Injurymentioning
confidence: 99%
See 3 more Smart Citations